Case Report: A Novel Genetic Mutation Causes Idiopathic Infantile Arterial Calcification in Preterm Infants - Yunfeng, Liu; Tongyan, Han; Jing, Wang; Xiaomei, Tong (Frontiers in Genetics, 2021)
Idiopathic infantile arterial calcification (IIAC), also known as generalized arterial calcification of infancy (GACI), is a heritable ectopic mineralization disorder that results in diffuses arterial calcifications and/or stenosis, which are attributed to mutations in the ENPP1 gene. In this case study, we report a case of IIAC in a two-months-old male preterm infant. The patient presented severe hypertension and seizures, further investigation revealed diffused calcifications and c.130C > T and c.1112A > T mutations in the ENPP1 gene. With biphosphonates, antihypertensive, and control epilepsy therapy, his blood pressure was maintained to 110–120/50–60 mmHg. Intellectual motor development retardation was anticipated in the patient. To the best of our knowledge, this is the first case in which a novel c.130C > T mutation in the ENPP1 gene has been identified and the administration of bisphosphonate to patients with IIAC has been assessed.